Pemanfaatan Pekarangan untuk Budidaya Tanaman Herbal dan Penyediaan Jet PAM sebagai Sumber Air Guna Meningkatkan Ekonomi Warga Mlopoharjo - Anggraini, Cicilia Clara Devi; Dewi, Danar Kristiana; Budiwati, Yulia; Paramitasari, Ratih; Fadloli, Fadloli; Bimo, Djoko Sri; Purbokusumo, Andreas Sang Aji (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity was carried out in Mlopoharjo Village, Wuryantoro District, Wonogiri Regency, Central Java, where the majority of the population works as farmers and ranchers. Based on data from Statistics Indonesia, around 60% of productive land is rice fields, while the rest is yards and plantations that have not been optimally utilized. The UT Surakarta Community Service Team sought to improve the welfare of the community through the cultivation of medicinal plants such as ginger, turmeric, and galangal in yards. Herbal plants were chosen because they are easy to cultivate, beneficial to health, chemical-free, inexpensive, and have high economic value. Additionally, these plants are suitable for cultivation during the dry season. To support sustainable cultivation, the team provides jet pumps as a water source for backyards, especially in areas prone to drought. This program is implemented through outreach and training, as well as seed distribution, so that the harvest can be consumed or sold to improve residents' economic conditions.